Models and Algorithms for Biomolecules and Molecular Networks - DasGupta, Bhaskar (UNITED STATES : Wiley-IEEE Press, 2016)
By providing expositions to modeling principles, theories, computational solutions, and open problems, this reference presents a full scope on relevant biological phenomena, modeling frameworks, technical challenges, and algorithms. -Up-to-date developments of structures of biomolecules, systems biology, advanced models, and algorithms -Sampling techniques for estimating evolutionary rates and generating molecular structures -Accurate computation of probability landscape of stochastic networks, solving discrete chemical master equations -End-of-chapter exercises.
3.1 Introduction, 79 -- 3.2 Principles of Monte Carlo Sampling, 81 -- 3.2.1 Estimation Through Sampling from Target Distribution, 81 -- 3.2.2 Rejection Sampling, 82 -- 3.3 Markov Chains and Metropolis Monte Carlo Sampling, 83 -- 3.3.1 Properties of Markov Chains, 83 -- 3.3.2 Markov Chain Monte Carlo Sampling, 85 -- 3.4 Sequential Monte Carlo Sampling, 87 -- 3.4.1 Importance Sampling, 87 -- 3.4.2 Sequential Importance Sampling, 87 -- 3.4.3 Resampling, 91 -- 3.5 Applications, 92 -- 3.5.1 Markov Chain Monte Carlo for Evolutionary Rate Estimation, 92 -- 3.5.2 Sequentail Chain Growth Monte Carlo for Estimating Conformational Entropy of RNA Loops, 95 -- 3.6 Discussion and Summary, 96 -- References, 97 -- Exercises, 99 -- 4 Stochastic Molecular Networks 103 -- 4.1 Introduction, 103 -- 4.2 Reaction System and Discrete Chemical Master Equation, 104 -- 4.3 Direct Solution of Chemical Master Equation, 106 -- 4.3.1 State Enumeration with Finite Buffer, 106 -- 4.3.2 Generalization and Multi-Buffer dCME Method, 108 -- 4.3.3 Calculation of Steady-State Probability Landscape, 108 -- 4.3.4 Calculation of Dynamically Evolving Probability Landscape, 108 -- 4.3.5 Methods for State Space Truncation for Simplification, 109 -- 4.4 Quantifying and Controlling Errors from State Space Truncation, 111 -- 4.5 Approximating Discrete Chemical Master Equation, 114 -- 4.5.1 Continuous Chemical Master Equation, 114 -- 4.5.2 Stochastic Differential Equation: Fokker -- Planck Approach, 114 -- 4.5.3 Stochastic Differential Equation: Langevin Approach, 116 -- 4.5.4 Other Approximations, 117 -- 4.6 Stochastic Simulation, 118 -- 4.6.1 Reaction Probability, 118 -- 4.6.2 Reaction Trajectory, 118 -- 4.6.3 Probability of Reaction Trajectory, 119 -- 4.6.4 Stochastic Simulation Algorithm, 119 -- 4.7 Applications, 121 -- 4.7.1 Probability Landscape of a Stochastic Toggle Switch, 121 -- 4.7.2 Epigenetic Decision Network of Cellular Fate in Phage Lambda, 123 -- 4.8 Discussions and Summary, 127 -- References, 128.
Print version record.
Keywords: Biomolecules; Structure-activity relationships (Biochemistry); Biomolecules; Structure-activity relationships (Biochemistry); SCIENCE / Life Sciences / Biophysics; Electronic books